1996
DOI: 10.1177/016502549601900207
|View full text |Cite
|
Sign up to set email alerts
|

Ideas about Parenting in Argentina, France, and the United States

Abstract: Central to a concept of culture is the expectation that different peoples possess different ideas and behave in different ways with respect to child rearing. In this study, we investigated ideas that Argentine, French, and US American mothers hold about their own and their husbands' actual child rearing, as well as what they consider to be ideal child rearing, in three parenting domains: social, didactic, and limit setting. For each domain, we analysed mothers' reports of their actual behaviours and of their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 25 publications
3
46
0
2
Order By: Relevance
“…Studies to date suggest parental knowledge is related to socioeconomic status (Tamis-Lemonda, Chen, & Bornstein, 1998), maternal education (Richman, Miller, & LeVine, 1992), and culture (Bornstein et al, 1996). Little is known about whether the level of knowledge parents possess is influenced by such things as parenting experience (i.e., number of children), age, support with childcare, financial support through public assistance, or living situations.…”
Section: Predictors Of Maternal Knowledgementioning
confidence: 99%
“…Studies to date suggest parental knowledge is related to socioeconomic status (Tamis-Lemonda, Chen, & Bornstein, 1998), maternal education (Richman, Miller, & LeVine, 1992), and culture (Bornstein et al, 1996). Little is known about whether the level of knowledge parents possess is influenced by such things as parenting experience (i.e., number of children), age, support with childcare, financial support through public assistance, or living situations.…”
Section: Predictors Of Maternal Knowledgementioning
confidence: 99%
“…Ogbu (1981) argued that even within the United States, views about competence diverge signi cantly and psychologists should use culturally relevant criteria of competence to assess minority children. Although few have followed his proposal, research on parents' beliefs about children has blossomed (Goodnow & Collins, 1990;Harkness & Super, 1992, 1996Siegel, 1985) and studies comparing parental beliefs across cultures have found signi cant intercultural and intracultural variation (e.g., Bornstein et al, 1996;Harwood, Schoelmerich, Ventura-Cook, Schulze, & Wilson, 1996).…”
mentioning
confidence: 99%
“…Bornstein et al, 1996) were used in this study, comprised of affective and responsive parenting behaviors. The scale was a 5 point Likert-type Scale (1=not at all to 5=very much so), thus total scores ranged from 6 to 30.…”
Section: Participantsmentioning
confidence: 99%